Shock wave overpressure history mapping using high-resolution distributed acoustic sensing - Masoudi, Ali; Lee, Timothy; Beresna, Martynas; Critchley, Richard; Brambilla, Gilberto; Denny, Jack (SPIE, 2025)
This study explored the use of high-resolution distributed acoustic sensing (HR-DAS) for measuring blast wave overpressures, addressing the limitations of conventional pressure transducers. Shock tube experiments were conducted to evaluate HR-DAS performance in capturing side-on blast overpressures, comparing its strain measurements with reference piezoelectric pressure transducers. The study examined the effects of sensing fibre orientation and mounting methods on sensor sensitivity. Results showed that HR-DAS strain histories aligned well with conventional pressure measurements. The findings demonstrate the feasibility of HR-DAS for blast wave sensing, highlighting its potential for further development and broader applications.
Keywords: 4006 Communications Engineering; 40 Engineering; 4009 Electronics, Sensors and Digital Hardware; Bioengineering; 4006 Communications engineering; 4009 Electronics, sensors and digital hardware; 5102 Atomic, molecular and optical physics; High-resolution; DAS; Distributed acoustic Sensor; Shock wave; Blast wave